2009
DOI: 10.1136/bjo.2008.144006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of reverse cholesterol transport proteins ATP-binding cassette A1 (ABCA1) and scavenger receptor BI (SR-BI) in the retina and retinal pigment epithelium

Abstract: Aims Excessive lipid accumulation in Bruch’s membrane (BrM) is a hallmark of ageing, the major risk factor for age-related macular degeneration (AMD). Retinal pigment epithelial (RPE) cells may utilise reverse cholesterol transport (RCT) activity to move lipid into BrM, mediated through ATP-binding cassette A1 (ABCA1) and scavenger receptor BI (SR-BI). Methods ABCA1 expression was assessed by reverse transcription polymerase chain reaction (RT-PCR) and western blotting of human RPE cell extracts. Lipid trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 20 publications
1
68
0
Order By: Relevance
“…ABCA1 mediates the efflux of cholesterol and phospholipids to lipid-poor apolipoproteins, which then form nascent HDL [27,28]. In a recent study, ABCA1 was shown to be expressed in the retina and retinal pigment epithelium [29]. Several studies have demonstrated an association between rs1883025 variants in ABCA1 and different stages of AMD in multiethnic populations.…”
Section: Discussionmentioning
confidence: 99%
“…ABCA1 mediates the efflux of cholesterol and phospholipids to lipid-poor apolipoproteins, which then form nascent HDL [27,28]. In a recent study, ABCA1 was shown to be expressed in the retina and retinal pigment epithelium [29]. Several studies have demonstrated an association between rs1883025 variants in ABCA1 and different stages of AMD in multiethnic populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are some differences between SR-BI and SR-BII, both proteins have been localized to the retinal ganglion cells and Müller cells as well as to photoreceptors ( 50,55 ). ApoA1 and ABCA1 were both detected in retinal ganglion cells and the outer plexiform layer ( 50,56 ). ApoA1 immunoreactivity was also observed to be associated with photoreceptor outer segments (most likely present in the inter-photoreceptor matrix (IPM), the extracellular matrix fi lls the subretinal space) and the inner segment of rods, but not cones, as well as with the apical face of RPE cells ( 50 ).…”
Section: Uptake and Intraretinal Exchange Of Cholesterol By The Retinamentioning
confidence: 99%
“…This close anatomical association between the RPE and photoreceptors is one of the factors that promotes the ability of the RPE to, on the one hand, provide nutrients and oxygen to the photoreceptor cells and, on the other hand, eliminate metabolic wastes generated by the neural retina, including those resulting from the shedding of outer segments tips and their subsequent phagocytosis and degradation by the RPE. The RPE cells express a variety of lipoprotein-specifi c and scavenger receptors: VLDL receptor ( 47 ), LDL receptor (LDL-R) ( 12,48,49 ), and the so-called scavenger receptors CD36 ( 48,(50)(51)(52)(53)(54), SR-BI, and BII ( 50,52,55,56 ). Interestingly, LDL-R was also localized to the endothelial cells of the choriocapillaris, the photoreceptor inner segments, retinal ganglion cells, and Müller cells ( 12 ).…”
Section: Uptake and Intraretinal Exchange Of Cholesterol By The Retinamentioning
confidence: 99%
“…Thus, most of the studied genes seem to be expressed as proteins in the retina. Mouse retina can now be compared with human retina ( 11 ), the retina of other species ( 10,14 ), and immunohistochemistry characterizations by others ( 35 ). Quantitative methodologies should be used to confi rm immunolocalizations.…”
Section: Statisticsmentioning
confidence: 99%